Specific mental disorder screening compilation may detect general mental disorders - Lívia Maria Bolsoni; Leonardo Moscovici; João Mazzoncini de Azevedo Marques; Antonio Waldo Zuardi (Revista Brasileira de Medicina de Família e Comunidade, 2018)
Objective: To evaluate whether a short compilation of screening tools for specific disorders could identify Mental or Emotional Disorders (MEDs) in the general population. Methods: We selected validated screening tools for the most prevalent MEDs. In order to be selected, these tools should maintain the psychometric properties of the complete instrument with a reduced number of items. These instruments were: Patient Health Questionnaire-2 (PHQ-2), Generalized Anxiety Disorder Scale-2 (GAD-2), item 3 of the Alcohol Use Disorders Identification Test (AUDIT), and three items on the Adolescent Psychotic-Like Symptom Screener (APSS-3). We called this compilation of screening tools Mini Screening for Mental Disorders (Mini-SMD). The study was divided in two phases. Firstly, 545 subjects were interviewed with the Mini-SMD and COOP/WONCA-Feelings at their residences. Subsequently, subjects who had agreed to participate (230) were reinterviewed with Mini-SMD, COOP/WONCA-Feelings and MINI interview. Test-retest reliability was calculated by Intraclass Correlation Coefficient (ICC). Receiver operating characteristic (ROC) curves were generated for the analysis of discriminative validity. Concurrent validity was calculated by analyzing the correlation between Mini-SMD and COOP/WONCA-Feelings. Results: The joint administration of screening tools for specific disorders showed sensitivities that ranged from 0.76 to 0.88 and specificities from 0.67 to 0.85. The ICC value for the total score of Mini-SMD was 0.78. The area under the curve was 0.84, with a sensitivity of 0.74 and specificity of 0.76 (for a cutoff ≥ 4). Conclusion: This study showed that a short compilation of screening tools for specific disorders can detect MEDs in general population.